Contemporary Management of the High-Risk Pulmonary Embolism: The Clot Thickens. (August 2019) - Reardon, Peter M.; Yadav, Krishan; Hendin, Ariel; Karovitch, Alan; Hickey, Michael
Pulmonary embolism (PE) is a common disease process encountered in the acute care setting. It presents on a spectrum of severity with the most severe presentations carrying a substantial risk of morbidity and mortality. In recent years, a wide range of competing treatment strategies have been proposed for the high-risk PE including new catheter-based and extracorporeal techniques, and management has become more challenging. There is currently no consensus as to the optimal approach to treatment. Contemporary management decisions are informed by the balance between the risk of deterioration and the risk of harm from intervention, within the available resources. This review will summarize the current evidence to better inform clinical decision-making in high-risk PE and highlight future directions in management.